A Pilot Classroom-Based Study of Attention and Working Memory Strategies for Primary-Aged Students. Issue 1 (29th April 2016) - Colmar, Susan; Davis, Nash; Sheldon, Linda
Abstract : An exploratory applied study, using a set of attention and working memory strategies specifically developed for students and named Memory Mates, was completed with normally developing students attending a primary school. Students in one classroom received the intervention, while the other classroom functioned as a control group. The study was experimental, with quantitative measures. Additional qualitative data was collected to facilitate the ongoing development of Memory Mates. A working memory instrument was used to rank students initially, and as a post-intervention measure for children with low working memory, with some gains in working memory observed in the experimental classroom students. Data were collected on academic achievement in reading, spelling, and maths. Post-intervention data analysis of the impact of the Memory Mates intervention showed no differences between the experimental and control groups for standardised academic measures. Several reasons are postulated for the lack of significant quantifiable change, chiefly the short period of intervention.